Eco-friendly nutrient from ocean : Exploring Ulva seaweed potential as a sustainable food source - Khan, Nida; Sudhakar, Kumarasamy; Rizalman, Mamat (Elsevier B.V., 2024)
Growing environmental concerns and a desire for health-conscious food choices are driving consumer demand for sustainable and ethical food sources. Ulva seaweed (genus Ulva, Phylum Chlorophyta) emerges as a promising candidate due to its rich nutritional profile, which includes proteins, carbohydrates, lipids, and antioxidants. This review explores the immense potential of Ulva seaweed as an eco-friendly and nutritious food source with promising applications in the food industry. Focusing on its viability as a sustainable solution, we explore Ulva's biochemical composition, potential health benefits beyond established nutrition, and its role in food product development. While challenges remain, including variability in nutrient content, efficient harvesting and processing methods, and ensuring food safety, Ulva's minimal environmental impact and high nutritional value make it a compelling alternative. Furthermore, recent studies reveal Ulva's unique compounds possess impressive health benefits, including antioxidant, antimicrobial, and antiviral properties, which offer exciting possibilities for human health. Furthermore, the integration of Ulva cultivation in Integrated Multitrophic Aquaculture (IMTA) systems demonstrates its feasibility for large-scale production while enhancing environmental sustainability. Additionally, recent studies reveal the impressive health benefits of seaweed's unique compounds, with properties like antioxidant, antimicrobial, and antiviral effects, offering exciting possibilities for human health. This review provides valuable insights for researchers exploring Ulva seaweed, a readily available natural resource that holds the potential to address global malnutrition without compromising the food ecosystem's health.